Rocket seed (Eruca sativa Mill) gum: physicochemical and comprehensive rheological characterization - Kutlu, Gozde; Akcicek, Alican; Bozkurt, Fatih; Karasu, Salih; Tekin-Cakmak, Zeynep Hazal (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
This study aimed to determine the physicochemical and rheological characterization of Rocket seed gum (RSG) as a plant-based natural gum. Moisture, ash, protein, monosaccharide composition, and pH value were determined. Mannose and galactose were the main monosaccharides with a ratio of (mannose/galactose) 1.52. The absorptions at wavenumber 2855 cm(-1) and 2922 cm(-1) indicate the presence of galactose and arabinose. RSG showed shear-thinning flow behavior at all concentrations. The K value of the RSG ranged between 0.24 and 6.31 Pa.s(n) and significantly increased with increased gum concentration. Hysteresis area was found 11.53-183.23 and increased with increasing gum concentration. The percentage recovery for the G' was significantly affected by gum concentrations and found as 42.54-81.20. RSG showed a solid-like structure, the storage modulus (G') was higher than the loss modulus (G '') in all frequency range. G' and G ''. value increased with increased RSG concentration. The physicochemical and rheological characterization indicated that RSG could be evaluated as thickeners and gelling agents in the food industry.
Keywords: rocket seed gum; sugar composition; rheology; FT-IR; FLOW BEHAVIOR; COMPOSITIONAL ANALYSIS; BETA-LACTOGLOBULIN; THIXOTROPY; PURIFICATION; OIL; HYDROCOLLOIDS; ASSOCIATION; EXTRACTION; Food Science & Technology